2021
DOI: 10.1002/ptr.7023
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic properties of lichen secondary metabolites

Abstract: Lichens are symbiotic organisms which are composed fungi and algae and/or cyanobacteria. They produce a variety of characteristic secondary metabolites. Such substances have various biological properties including antimicrobial, antiviral, and antitumor activities. Angiogenesis, the growth of new vessels from pre-existing vessels, contributes to numerous diseases including cancer, arthritis, atherosclerosis, infectious, and immune disorders. Antiangiogenic therapy is a promising approach for the treatment of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Yang et al also showed tamidoline has anti-cancer properties against colorectal cancer cells [ 31 ]. Many lichen-derived acids have acceptable anti-cancer properties, so some of these compounds, such as lecanoric acid and vulpinic acid, are much more effective than conventional drugs in reducing thyroidoxin levels [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al also showed tamidoline has anti-cancer properties against colorectal cancer cells [ 31 ]. Many lichen-derived acids have acceptable anti-cancer properties, so some of these compounds, such as lecanoric acid and vulpinic acid, are much more effective than conventional drugs in reducing thyroidoxin levels [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, usnic acid in U. longissima is found in high concentrations and is evidenced with a significant effect on different cancer cell lines [37]. As for other chemical compounds, atranol was reported as a biologically active constituent of several lichens [38] including Stereocaulon azoreum and Stereocaulon vesubianum [39,40], and in Antarctic lichens in Everniopsis trulla [41], while barbatolic acid reported in Bryoria lichens [42] was reported to be active against breast cancer [43], showed antiangiogenic effects [44], and was previously reported in H. lugubris [45] while the compound 5,7-dihydroxy-6-methylphthalide was only reported to occur in Usnea florida [46] and Usnea antarctica [41]; the concentration of both compounds was 85.833 and 49.374 per gram of lichen, respectively (Table 2).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Due to the wide variety of secondary metabolites identified from lichens, these organisms can be viewed as promising natural product libraries for new bioactive molecule discoveries. Indeed, over 300 secondary metabolites have been characterized from lichens, including depsides, depsidones, dibenzofurans, xanthones, among others, with antibacterial, antiviral, antifungal, insecticidal, antiangiogenic, anticancer, and other properties (reviewed in [ 190 , 193 , 194 ]). An obvious challenge to the use of lichens as microbial cell factories to produce these metabolites is slow growth, technical difficulty of in vitro culture, and a lack of molecular tools [ 193 ].…”
Section: Interspecies Communicationmentioning
confidence: 99%